Internationalization of indoor positioning platform firms : Insights from loose coupling theory - Ojala, Arto; Fraccastoro, Sara; Gabrielsson, Mika (Hawaii International Conference on System Sciences, 2024)
Indoor positioning platforms are gaining popularity in various indoor environments, serving multiple purposes such as navigation, asset tracking, proximity marketing, and indoor analytics. However, the diversity of potential use cases and technical complexity makes these platforms challenging to internationalize across different markets and customer segments. Drawing on the characteristics of digitalization framework and the loose coupling theory, we analyze and explain the phenomenon in an indoor positioning platform firm. Our findings reveal that platforms’ openness and digital affordances played a pivotal role in its internationalization by enabling customization of the service to meet the needs of foreign markets and industry segments. Both loose and tight couplings were essential for the platform's global expansion. We also revealed the dynamic nature of couplings in the firm's internationalization journey.
Keywords: Digital platforms; Characteristics of digitalization; Loose coupling theory; Case study; indoor positioning; fi=Kansainvälinen liiketoiminta|en=International Business|